2018
DOI: 10.1016/j.mechmat.2018.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Finite element modelling effects of inter-yarn friction on the single-layer high-performance fabrics subject to ballistic impact

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain. Highlights  Higher inter-yarn friction will make … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…The theoretical fabric behavior is usually investigated using finite element modeling based on the geometry of textile structures. The geometry of fabric structures could be obtained by parametric modeling of the real geometry (Chu and Chen, 2018;Wu and Li, 2019) or by computed X-ray tomography observation (Naouar et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The theoretical fabric behavior is usually investigated using finite element modeling based on the geometry of textile structures. The geometry of fabric structures could be obtained by parametric modeling of the real geometry (Chu and Chen, 2018;Wu and Li, 2019) or by computed X-ray tomography observation (Naouar et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…While the PD contributes more in both 2D fabric panels. According to Chu et al [28], the primary yarns that in direct contact with the projectile tends to fail by plastic fracture damage, while the secondary yarns interlaced with the primary yarns participate in energy absorption by tensile failure during the penetration process. The fact that SE contributes more in 3D fabric indicates that there are more secondary yarns involved in energy absorption of the fabric, which leads to a wider fabric deflection and an improved energy absorption capability.…”
Section: Energy Absorptionmentioning
confidence: 99%
“…Numerical simulations and finite element analysis have revealed that the greater the friction between yarns, the higher the energy consumption under an impact. Wang et al asserted that projectiles took a longer time to penetrate fabrics with larger inter-yarn friction. Moreover, yarn-to-yarn friction plays an important role in the stress distribution of primary and secondary yarns .…”
Section: Introductionmentioning
confidence: 99%